(3eQBI GdReGf aj JhGQjN GdCYjGfs - (3jhSa Hf pbrRoChrZpdj (B- (3Ch bRZdj (B- (3GHf YHO Gddg, CHh GdeXaQ, TeS GdOjf, SHW CHj GdaQL GHf GdLhRj,J (B654 (3g` s ((3CMeO Hf (B( (3GdYde (B) (3GdCbSeGhi GdeYQha HGdMdjei s)
(3ChdgG (B:s
(3jHOC CKfGA (B218 (3HYfhGf PcQ hRQGA GdeCehf hMLGHg hbVGJg Hbhdg (B: (3Chd eG hRQ dg HNQGSGf GdaVd Hf Sgd s
(3BNQgG (B:s
(3jfJgi CKfG SfI (B253 (3Hbhdg (B: (3hbGd eMeO Hf YHO Gddg Hf WGgQ cfJ hGbakG Ydi QCS CHj hYfOg CMeO Hf MfHd Je GdLRA GdKGdK YTQ HMeO Gddg hjJdhg ai GdLRA GdQGHY YTQ haGI hUja GdJQci s
(3fSNI KGfjIs
(3cJHJ gPg GdfSNI HQSe EHQGgje Hf Ydi Hf eMehO Hf LhG eQOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B246 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B324s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B224 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B589 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B179 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs